Penggunaan Media Foto Dalam Menulis Kalimat Sederhana Bahasa Jerman - Kamelia Kamelia; Nurming Saleh; Laelah Azizah (Universitas Negeri Makassar, 2022)
Abstract. This research was conducted to obtain data and information about students' ability to write simple sentences in German using Photo Media. This research is an experimental research. The population of this study were all students of class XI IPS SMAN 11 Makassar which consisted of 3 classes with a total of 120 people. The sample of this study consisted of two classes as follows: class XI IPS 1 with 20 students as the experimental class and class XI IPS 3 with 20 students as the control class. Samples were selected randomly (Random Sampling). The research data was obtained through a simple sentence writing test with the theme Die Familie. Data analysis by t-test. The results of data analysis showed tcount 4.78 > ttable 2.03 at a significant level of 0.05. The results of this study indicate that the use of Photo media is effective in writing simple sentences in German for class XI IPS 1 students of SMAN 11 Makassar.Keyword: Effectiveness, Photo Media, Writing sentences, German